G20 Endorsement in Post Crisis Global Governance: More Than a Toothless Talking Shop?. (May 2015) - Eccleston, Richard; Kellow, Aynsley; Carroll, Peter
Research Highlights and Abstract This article Highlights how G20 'endorsement' promotes and enhances the legitimacy of specialist technical agencies and organisations Provides a case study highlighting the impact of G20 endorsement on the OECD's international tax transparency agenda Develops a mid-level theory of G20 endorsement in order to analyse this emerging form of authority in global governance The G20 Leaders' Forum has been touted as 'The world's premier forum for promoting global cooperation', yet beyond this rhetoric the track record of the G20 is varied leading critics to claim sit is little more than a 'toothless talkshop'. We argue that such sweeping generalisations are difficult to sustain in the light of evidence from some issue arenas in which the G20 has been active. This article draws on the extant literature on the 'Gs'and network governance in an attempt to theorise and explain the G20's endorsement function, or its capacity to promote and legitimise the work of specialised organisations and networks. We build on the extant literature using a semi-inductive method focusing on the G20's endorsement of the OECD's international tax transparency agenda to develop a mid-level framework for analysing this important source of authority in global governance.